Pembuatan Biopori sebagai Resapan di SDN II Cangkring, Krembung, Sidoarjo: Making Biopores as Absorption at SDN II Cangkring, Krembung, Sidoarjo - Sucahyo, Muhammad Aji; Islamiah, Rahma Nadia; Fahrezy, Muhammad Daffa Attalla; Sawitri, Aristha Purwanthari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Cangkring Village, Krembung, Sidoarjo, is one of the villages that is always affected by floods when the rainy season comes. One method that can be applied to reduce flooding is through biopores. The purpose of making Biopori Holes is to reduce the occurrence of waterlogging in an area and reduce the volume of organic waste that can be used as organic fertilizer. Biopori Infiltration Hole is a water infiltration facility used to overcome flooding by accelerating water absorption into the ground. Increasing the ability of the soil to absorb water can minimize the chance of surface runoff and reduce the potential for flooding. Biopori can also reduce the volume of organic waste that needs to be appropriately managed. Based on the problems in Cangkring Village, the team carried out service through socialization and training in making biopores. The target of this activity is students of grade IV and V SDN II Cangkring, Krembung, Sidoarjo. This activity aims to train students to know how to overcome waterlogging and use organic waste as fertilizer so that students care more about the surrounding environmental conditions.